Pengaruh Pertumbuhan Ekonomi, dan Jumlah Penduduk dan Tingkat Kesehatan Terhadap Kemiskinan di Kabupaten Minahasa Selatan - Aurelia Priskila Mariani Watung; Josep Bintang Kalangi; Jacline I. Sumual (PT. Hasba Edukasi Mandiri, 2025)
Economic development is the main goal of a country, where increased development reflects the progress achieved by the country. One of the indicators of the success of economic development is the increasing economic growth in a region. However, economic development is often faced with challenges such as poverty, which need to be overcome or at least reduced. This study aims to analyze the influence of economic growth, population number, and health level simultaneously on the poverty rate in South Minahasa Regency. The data used in this study is secondary data from the Central Statistics Agency of South Minahasa Regency during the period 2010–2023. The method used is multiple linear regression analysis. The results of the study show that economic growth has a positive but not significant influence on the poverty rate in South Minahasa. The number of population has a positive and significant influence, while the level of health has a negative and significant influence on the poverty rate in South Minahasa.